1952
DOI: 10.1177/004051755202200403
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Capacities of Fibers in Water

Abstract: Swelling in water is one of the important fundamental properties of cellulosic fibers, and is also a factor in determining the proper fiber for a specific utilization. An example of this is the selection of cottons for self-sealing fabrics. Since existing techniques for measuring swelling capacities, as they have been used, are tedious and time-consuming, it was desired to find a rapid method which would be sensitive enough to establish, with certainty, small differences in swelling capacity due to variety, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1953
1953
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…When fur is spinning, the associated centrifugal force competes with surface tension to decrease the height of the water column to a modified Jurin's height H ¼ 2scos u e /rRv 2 d. Using the definition of RMC, we may write RMC ¼ H/H initial þ D, where D is a free parameter used for fitting the asymptote in figure 5b. This parameter D cannot be predicted with our simple model, as it represents the moisture that soaks into the rough surfaces of the hair and skin, and cannot be removed even under extreme centrifugal forces [44][45][46][47]. The remaining moisture content simplifies to Using our measured trends in moisture content in figure 5b, we may quantify the benefits of the animal's loose dermal tissue, observed in figure 1c.…”
Section: Physical Basis Of Residual Moisture Contentmentioning
confidence: 99%
“…When fur is spinning, the associated centrifugal force competes with surface tension to decrease the height of the water column to a modified Jurin's height H ¼ 2scos u e /rRv 2 d. Using the definition of RMC, we may write RMC ¼ H/H initial þ D, where D is a free parameter used for fitting the asymptote in figure 5b. This parameter D cannot be predicted with our simple model, as it represents the moisture that soaks into the rough surfaces of the hair and skin, and cannot be removed even under extreme centrifugal forces [44][45][46][47]. The remaining moisture content simplifies to Using our measured trends in moisture content in figure 5b, we may quantify the benefits of the animal's loose dermal tissue, observed in figure 1c.…”
Section: Physical Basis Of Residual Moisture Contentmentioning
confidence: 99%
“…Reported values of percent swelling of cotton, corrected for lumen area, ranged from 31-33o7o for cotton of different varieties and maturity and 65~ for viscose rayon fibers (Stamm 1964;Moore et al 1950;Welo et al 1952). No such data has been obtained for wood pulp.…”
Section: Cellulosementioning
confidence: 99%
“…In analyzing our data in their Table III, Welo et al [9], using their theoretical model and some regain data from their desiccation rate technique measurements [8], arrived at values for the capillary water. In a recent paper [ 1 ] , Ashpole suggested that the saturation regains are very much nearer to the centrifuge values than their desiccation rate data suggest.…”
Section: Moisture Gradients In Centrifugedmentioning
confidence: 99%